Infant Intakes of Human Milk Amino Acids Are Associated With Maternal Obesity and Infant Growth. (7th June 2021) - Saben, Jessica; Sims, Clark; Pack, Lindsay; Lan, Renny; Andres, Aline
Abstract: Objectives: Branched chain amino acids (AA) (BCAAs: leucine (Leu), isoleucine (Ile), and valine) and aromatic AA (AAAs: phenylalanine (Phe) and tyrosine (Tyr)) have been hypothesized to take part in early-life metabolic programing. To date studies testing the effect of early-life AA consumption on metabolic programing have been focused on formula milk proteins, where increased consumption was associated with obesity risk. However, a knowledge gap exists regarding how variations in human milk (HM) free AA concentrations might impact child growth. Here, we aimed to characterize HM free AA concentrations and infant intakes of HM AAs from women with obesity (OB) compared to those with normal weight (NW). We hypothesized that infants born to women with OB would consume greater amounts of HM BCAAs and AAAs, which would be positively associated with their growth. Methods: HM samples were collected at 0.5 months (0.5M; n = 151), 2 months (2M; n = 129), and 6 months (6M; n = 93) postpartum from NW (body mass index (BMI) = 18.5 – 24.9 kg/m 2 ) and OB (BMI > 30 kg/m 2 ) mothers. HM free AA were quantified at each timepoint via mass spectrometry. Infant HM intake, anthropometrics and body composition were assessed at each timepoint. Linear mixed effect models examined the relationships between maternal BMI and HM AA composition, HM AA intake, and infant growth over the first 6Ms postpartum. Models were adjusted for maternal race, breastfeeding exclusivity, infant sex and infant age. Results: Concentrations of Ile, Leu, and AAAs were higher (p < 0.05) across all timepoints in HM from women with OB compared to those with NW. Infant intakes, normalized to kg body weight, of these AAs were only significantly higher at 2M. Maternal BMI was negatively associated (p < 0.05) with infant intakes of HM asparagine, cystine, and histidine and positively associated with Ile, Leu, and AAAs intakes across timepoints. Infant intakes of HM Ile (b = −0.083), Leu (b = −0.045), and proline (b = -0.024) were negative predictors of infant weight-for-age z-scores over the first 6M postpartum (p < 0.05). Conclusions: Maternal obesity is associated with increased BCAA and AAA infant exposures over the first 6M of life. However, the impact of these AAs on infant growth are not consistent with observations made with infant formulas. Funding Sources: USDA ARS Project # 6026-51, 000-010-05S and 6026-51, 000-012-06S.